Evaluation of superovulation responses in some domestic ewe breeds - Ayşe Merve Köse; Sakine Ülküm Çizmeci; İrfan Tur; Mehmet Güler (Eurasian Journal of Veterinary Sciences)
Aim: To compare the superovulation technique on some local-breed ewes. Materials and Methods: Daglic (n=19), Herik (n=27) and Norduz (n=30) breed were used in this study as material. Ewes were treated with intravaginal progesterone sponge for 12 days during breeding season and administered reducing doses of FSH. After sponge removal, ewes in estrus were mated with fertil rams and given 750 IU hCG. Ovarian response was assessed 7 days after mating and oviducts were flushed for embryo collection by laparoscopy. Results: Superstimulation rates and superovulation response of Daglic, Herik and Norduz ewes were 57.9%-63%, 78%-66% and 80%-76%, respectively. Average number of corpus luteun and embryo of Daglic, Herik and Norduz ewes were 7.71-4.29, 9.30-3.00 and 10.3-3.33, respectively. Minimum fertilization (embryo) and recovery rates (embryo + UFO) were 55% and 68% for Daglic, 32% and 63% for Herik, and 32% and 62% for Norduz, respectively. There was no statistically significance in the investigated values (p>0.05). Conclusion: It may be stated that administered superovulation technique has similar effect on the three ewe breeds.